Gender differences in the effects of childhood psychopathology and maternal distress on mental health in adult life. - Flouri, E; Malmberg, L (2011)
PURPOSE: To investigate gender differences in how emotional and behavioural problems (hyperactivity, emotional problems, and conduct problems) and maternal psychological distress, all measured at three time points in childhood (ages 5, 10, and 16), predict psychological distress in adult life (age 30). METHODS: Longitudinal data from 10,444 cohort members of the 1970 British Cohort Study (BCS70) were used. RESULTS: Emotional problems in adolescence tended to be more strongly associated with adult psychological distress in men than in women. No gender differences in the association of adult psychological distress with maternal psychological distress in adolescence were found. In childhood and adolescence boys' externalizing behaviour problems tended to show more homotypic continuity than girls', but all heterotypic continuity (although very little) of behaviour problems was seen in girls. Maternal psychological distress in childhood tended to have a stronger effect on girls' than boys' emotional problems in adolescence. CONCLUSIONS: In general there was little evidence for gender differences either in the association of adult psychological distress with adolescent psychopathology or in the association of adult psychological distress with maternal psychological distress in adolescence. The continuity of emotional problems from childhood to adolescence to adult life was strong and similar for both sexes.